A Multi-source Localization System for Driverless Material Transport in Mixed Indoor and Outdoor Areas - Herbert, Meike; Zwingel, Maximilian; Czapka, Christian; Franke, Jörg (Production at the Leading Edge of Technology, 2021)
To ensure material supply in production, the focus of research and development is on flexible, automated intralogistics solutions. The automation of material transport in mixed indoor and outdoor environments enabling transport processes between factory buildings is still challenging. The seamless localization of transport vehicles with the required accuracy is a core issue for navigation. While global navigation satellite systems can be used outdoors, other approaches like wireless networks or light detection and ranging technology are applied indoors. Additional sensors e.g. incremental encoders or inertial measurement units are used to create a multi-source localization system, which can adapt to the ideal mix of sensor sources, especially in transition areas. In this paper, a localization approach for driverless transport vehicles is presented in detail including applied methods for data fusion and implementation. The localization approach is validated using a tow truck equipped with sensors for autonomous transport.
Keywords: Intralogistics; Autonomous material transport; Localization

An Economic Solution for Localization of Autonomous Tow Trucks in a Mixed Indoor and Outdoor Environment Using a Node Based Approach - Zwingel, Maximilian; Herbert, Meike; Lieret, Markus; Schuderer, Peter; Franke, Jörg (Production at the leading edge of technology, 2020)
Flexible intralogistics solutions are basic components to enable classic manufacturing companies to compete in dynamic and global production networks. Developments in the field of autonomous road traffic technology and the increasing availability of cost-efficient sensors allow the economic use of autonomous systems in various industrial sectors. One of the subareas of autonomous systems with economic and technological potential is the intralogistics material supply with driverless transport systems. While the usage between buildings of such systems is not yet economically feasible, development of cost-efficient sensors from other markets are opening up new approaches in this area of operation. Localization and navigation, which must work seamlessly in mixed indoor and outdoor usage scenarios, are particularly critical to the success of autonomous systems. In this paper, a solution for the localization and navigation of autonomous driverless transport systems in a mixed indoor and outdoor scenario is proposed. It focuses on the use of cost-efficient sensors to enable a mostly infrastructure-independent localization of each system. The proposed solution is validated and a first approach for a dynamic fusion of localization data is don
Keywords: AGVs; Autonomous mobility; Cost-efficient sensors

Anwendung etablierter Vorgehensweisen der Softwareentwicklung in der produzierenden Industrie. Systematische Methoden - Auswahl bei der Digitalisierung - Selmaier, Andreas; Martens, Benedikt; Sjarov, Martin; Kuhn, Marlene; Herbert, Meike; Franke, Jörg (wt Werkstattstechnik - Online, 2020)
Digitalization projects are software projects. Less suitable for such projects are sequential planning methods often used in conventional project management, as application-specific requirements and interdependencies of facilities and IT systems considerably increase overall complexity. Therefore, this paper presents an approach for the systematic selection of suitable management methods for digitalization projects, which adds iterative procedures from software development to traditional project planning in the production environment.
CRIS-Team Scopus Importer:2020-07-31

A systematic approach for planning, analyzing and evaluating internal material provision - Herbert, Meike; Heinlein, Pascal; Fuerst, Jens; Franke, Jörg (FAIM 2021, 2021)
CRIS-Team WoS Importer:2022-10-28

Automatische Identifikation mittels RFID - Rückverfolgbarkeit von Fertigungshilfsmitteln in der Produktion von Hochleistungsröntgenstrahlern - Herbert, Meike; Stirm, Julian; Hofmann, Christian; Fürst, Jens; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2022)
Modern technologies are a key enabler for the automatic identification of objects in production to ensure quality-related traceability of components or manufacturing equipment. This article presents a possible solution for the traceability of equipment, tools and measuring devices by applying a RFID system in the production of high-performance X-ray tubes and discusses the results of durability analysis.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Identification Systems; RFID; Lifetime; Traceability; X-Ray

Der Digitale Zwilling als echtzeitnahes Fertigungsabbild - Selmaier, Andreas; Sjarov, Martin; Herbert, Meike; Distler, Johannes; Fürst, Jens; Franke, Jörg (Simulation in Produktion und Logistik 2021, 2021)
In the course of the fourth industrial revolution, a multitude of new digital applications are being introduced along the entire life cycle of production systems. The structures of the classic automation pyramid are being softened and replaced by hybrid and decentralised structures in order to allow data and information to flow flexibly directly to where they are needed. For decision making processes in the manufacturing environment, a comprehensive overview of the factory and its current state is crucial. For this, specialised solutions are required to provide people intuitive access to the digital factory. The digital representation including enrichment with actual data falls under the paradigm "digital twin", which in relation to mechatronic manufacturing systems can be systematized by means of the Digital Twin Structure Model (DTSM). The article discusses a corresponding solution in the "proof-of-concept" status. The underlying concept as well as a real-world application are presented accordingly. Furthermore, the added value and future potentials are laid out.<br
Keywords: Digitaler Zwilling; Digitale Fabrik; Industrie 4.0

DESIGNING A FUTURE-ORIENTED STUDY PROGRAM IN ELECTROMOBILITY FOR INTERNATIONAL STUDENTS - Nasarow, Alexander; Herbert, Meike; Kreis, Oliver (18. Ingenieurpädagogischen Jahrestagung 2023, 2023)
Based on global challenges like climate change, a new international engineering study program "e-mobility-ACES" is introduced at the Friedrich-Alexander-University of Erlangen-Nuremberg (FAU). The aim is to develop an attractive and future-oriented study program with focus on internationalization and sustainability. In this paper, we present a detailed procedure for designing this new study program. Since international study programs may lead to several issues, also solutions for these issues are presented, leading to recommendations for the future design of large-scale study programs to help other universities with similar issue

Effect of the Motion Pattern on the Turbulence Generated by an Active Grid - Herbert, Meike; Skeledzic, Tanja; Lienhart, Hermann; Ertunc, Özgür (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2021)
In the field of turbulence research, many experiments are performed using turbulence generated under reproducible conditions. In the past mostly static grids having a fixed blockage were adopted, but in order to generate turbulence with high intensity and high turbulence Reynolds numbers, so called active grids can be used. Therefore, an experimental study has been carried out to investigate the effect of the motion pattern on the turbulence generated by an active grid with individually controllable paddles in the wind tunnel. Measurements were performed using the hot-wire technique. In comparison to former experiments, modifications of the active grid had been made concerning the arrangement of the paddles. The results show that the homogeneity of the turbulence could be improved using the modified grid. Turbulence Reynolds numbers could reach values up to 540. In order to produce even higher integral time scales or higher turbulence Reynolds numbers, synchronous movement of adjacent paddles was tested but did not show the intended improvements. In this paper, the results of the experimental study are presented in more detail.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Active grid; Experimental study; Turbulence

Hybrid Environment Reconstruction Improving User Experience and Workload in Augmented Virtuality Teleoperation - Blank, Andreas; Kosar, Emir; Karlidag, Engin; Guo, Qiang; Kohn, Sebastian; Sommer, Oliver; Walter, Jonas; Herbert, Meike; Seßner, Julian; Querfurth, Frank; Metzner, Maximilian; Franke, Jörg (Procedia Manufacturing, 2021)
Concurrent with autonomous robots, teleoperation gains importance in industrial applications. This includes remote intervention scenarios and human-robot-cooperation during complex or harmful tasks operated from a distance. For an efficient teleoperation, an interface achieving a good user experience and relieving workload of the operators is decisive. Whereas virtual reality allows a spatial integration, environment reconstruction is often based on point clouds in combination with pre-known object models. Challenges exist in spatial representation, through bandwidth limitations and sensor interferences. Furthermore, the potential of knowledge augmentation for workload improvement is often not fully utilized. To overcome these challenges, we present a hybrid environment reconstruction method, which is adaptive regarding the integration of different data sources as well as their derived semantic information levels. For evaluation, a user study is performed. Thereby known procedures to measure usability, immersion, user experience and operator workload serve for evaluation and comparison.<br
Keywords: Teleoperation; Virtual Reality; Environment Reconstruction; Knowledge Augmentation; Human-in-the-Loop

Potenziale zur Produktionsautomatisierung. Systematische Vorgehensweise zur Identifikation von Automatisierungsprojekten - Herbert, Meike; Selmaier, Andreas; Hefner, Florian; Franke, Jörg (wt Werkstattstechnik - Online, 2020)
Unternehmen der produzierenden Industrie, insbesondere der deutsche Mittelstand, sind bei der digitalen Transformation mit vielen Herausforderungen konfrontiert, beginnend mit der Analyse und Identifikation geeigneter Automatisierungsprojekte. In dem Beitrag wird eine ganzheitliche Vorgehensweise vorgestellt, um Potenziale für eine Automatisierung in Produktion und Logistik zu erkennen und konkrete Projekte zu definieren.<br
Keywords: Automatisierung; Industrie 4.0; Strategie

Robot-based automated production of wrapped connections with single solid round wires - Hefner, Florian; Herbert, Meike; Sjarov, Martin; Süß-Wolf, Robert; Franke, Jörg (Production at the leading edge of technology, 2019)
The solderless wrapping process is an electrical connection technology. It is mainly used in applications which require high reliability, such as the aerospace industry. A single solid conductor is wrapped around a connecting terminal. The process is currently being realized manually and the worker's qualification highly determines the overall process quality and efficiency. The challenges of this specific task include the handling of the flexible wire, the production process of standard-conforming wrapped connections and the required positioning accuracy of the tool relative to the wrappost. An automation of the production process is essential to meet the increasing quality and efficiency requirements of modern production environments, however, available solutions still highly rely on the operator and therefore lack the aspired automation degree. To enable the automated production of wrapped connections, a lightweight robot is equipped with several components. In this paper, the design of the whole system, including the newly developed robotic end-effector, is presented. The main components are two wrapping tools, each driven by an electric motor and attached to an electric slide. The device can be moved onto the wrappost extending the electric slide. A wire feeder realizes the conveying movement of the wire. Moreover, an optical sensor is used to determine the wrappost's position and orientation. The newly developed system enables the automated production of wrapped connections conforming to standards.<br
Keywords: wrapped connections; robot-based automation; flexible manufacturing

SETTING UP AN ENGINEERING "PILOT STUDY PROGRAM" IN E-MOBILITY FOR INTERNATIONAL STUDENTS: ISSUES AND SOLUTIONS - Herbert, Meike; Nasarow, Alexander; Kreis, Oliver (Proceedings of the 51th Annual Conference of The European Society for Engineering Education SEFI: Engineering Education for Sustainability, Dublin, 2023)
This practice paper presents the issues and solutions in introducing a new international engineering study program at a German university that attracts especially non-European students. The master’s program electromobility with the four majors Artificial Intelligence and Autonomous Driving, Connectivity, E-Powertrain and Sustainable Mobility & Production Technology was newly introduced in the winter semester 2022/23. It combines the expertise of all engineering departments like mechanical engineering, electrical engineering, computer science and artificial intelligence, materials science and chemical engineering to offer a modern and attractive engineering education for sustainability in an ecologic and economic important field. The high amount of applications with more than 1600 applicants per semester shows the high visibility and attraction of this study program. As the international master’s program is offered in English language, especially students e.g. from India, Pakistan or Bangladesh who already have a bachelor’s degree taught in English language are interested in this program. The selection of future students out of an extremely high number of applications is challenging, while this process has to be completed in a very short period of time. With this high number of international students, further issues occur regarding visa application, housing and other organizational aspects. Practical solutions are presented in this paper that lead to transferable recommendations for the future design of such large-scale study programs for other universitie

Systematische Methodenauswahl bei der Digitalisierung - Selmaier, Andreas; Martens, Benedikt; Sjarov, Martin; Kuhn, Marlene; Herbert, Meike; Franke, Jörg (Werkstattstechnik, 2020)
Digitalisierungsprojekte sind Softwareprojekte. Sequentielle Planungsmethoden, wie sie im konventionellen Projektmanagement überwiegend Anwendung finden, eignen sich jedoch nur bedingt für diesen Projekttyp, da die anwendungsspezifischen Anforderungen sowie die Abhängigkeiten der Anlagen und IT-Systeme untereinander zu einem erheblichen Anstieg der Gesamtkomplexität führen. In diesem Beitrag wird daher ein Ansatz zur systematischen Auswahl geeigneter Projektmanagementmethoden für Digitalisierungsprojekte vorgestellt, welcher die traditionelle Projektplanung im Produktionsumfeld um iterative Vorgehensweisen aus der Softwareentwicklung ergänz
Keywords: Produktionsmanagement; Digitale Fabrik; Industrie 4.0

Two-stage robotic bin picking of small metallic objects - Herbert, Meike; Bach, Paul; Lieret, Markus; Fürst, Jens; Franke, Jörg (Annals of Scientific Society for Assembly, Handling and Industrial Robotics 2022, 2023)
Robotic grasping of small metallic objects such as bolts is a challenging task due to the small dimensions and textureless reflective surfaces. Depth images acquired of such objects are often noisy and error-prone. In addition, overlapping of parts occur as they are provided randomly oriented in a box such as a small load carrier. To overcome the limitations of existing solutions for bolt separation, a flexible and costeffective system is developed using an industrial robot and a magnetic gripper. In a two-stage procedure, the bolts are first grasped blindly from a box and placed on a flat surface. In the second step, object detection and pose estimation is performed and the individual bolts are grasped and inserted into a fixture, so that finally the bolts are in a defined position. Industrial use cases for this system are the automated preparation of bolts for robotic screwing processes or automated commissioning of small objects for assembly tasks. The methodology, implementation and evaluation of the proposed solution is presented in this paper.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bin picking; Convolutional neural network; Magnetic gripper; Object detection